Implementasi Tata Tertib Sekolah dalam Optimalisasi Budaya Disiplin Siswa Di Madrasah Aliyah Muhammadiyah Nangahure - Fitriah Fitriah; Trisakti Handayani; Abdulkadir Rahardjanto (Jurnal Kebijakan dan Pengembangan Pendidikan, 2015)
Abstract: This study aims to describe the implementation of school rules in optimizing the culture of student discipline, along with the obstacles encountered and the solutions implemented in the Muhammadiyah Nangahure Aliyah Madrasah. This research is a qualitative descriptive study. The subjects of this study were the principal, teachers, and students. Data collection was obtained through observation, interviews, and documentation. Data analysis using data reduction, data display and conclusion drawing. The validity checking technique uses source triangulation. The results of the study show that the principal in implementing discipline in optimizing the culture of student discipline is carried out through the application of regulations, penalties, and rewards. The value of discipline is consistent in its application for students. The application of punishment and rewards made by school principals and teachers in the form of coaching to students. Teachers to optimize the culture of student discipline at school through advice to always be disciplined, give direct examples and familiarize children with disciplined life through four disciplinary elements namely fixed rules, strict punishment appreciation, and consistency. Constraints faced are lack of awareness or concern for parents about education and lack of teacher discipline at school.Keywords: School rules, Character, Discipline culture Abstrak: Penelitian ini bertujuan untuk mendeskripsikan implementasi tata tertib sekolah dalam optimalisasi budaya disiplin siswa, beserta kendala–kendala yang dihadapi serta solusi yang diterapkan di Madrasah Aliyah Muhammadiyah Nangahure. Penelitian ini merupakan penelitian deskriptif kualitatif. Subjek penelitian ini adalah Kepala sekolah, guru dan siswa.Pengumpulan data diperoleh melalui observasi, wawancara dan dokumentasi. Data analisis dengan menggunakan reduksi data, display data dan penarikan kesimpulan. Teknik pemeriksaan keabsahan menggunakan triangulasi sumber.Hasilpenelitian menunjukkan bahwa kepala sekolah dalam mengimplementasikan tata tertib dalam optimalisasi budaya disiplin siswa dilakukan melalui penerapan peraturan, hukuman dan penghargaan. Nilai disiplin sudah konsisten penerapannnya bagi siswa. Penerapan hukuman dan penghargaan yang dilakukan kepala sekolah dan guru dalam bentuk pembinaan kepada siswa.Guru dalam upaya mengoptimalkan budaya disiplin siswa di sekolah melalui nasehat untuk selalu disiplin, memberi contoh langsung dan membiasakan anak hidup disiplin melalui empat unsur disiplin yaitu peraturan yang tetap, hukuman tegas, penghargaan dan konsistensi. Kendala yang dihadapi yaitu kurangnya kesadaran atau kepedulian orang tua terhadap pendidikan dan kurangnya disiplin guru di sekolah.Kata kunci: Tata tertib sekolah, karakter, Budaya disiplin